Peran Financial Self-Efficacy dalam Memediasi Pengaruh Literasi Keuangan, Pendidikan Keuangan Keluarga, dan Teman Sebaya terhadap Perilaku Pengelolaan Keuangan - Nurjannah Nurjannah; Hikmayani Subur (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2026)
This study aims to examine and analyze the role of financial self-efficacy as a mediating variable in the influence of financial literacy, family financial education, and peers on the financial management behavior of students at the Faculty of Economics and Business, Universitas Negeri Makassar. This is a quantitative study with an explanatory approach. The population consists of active FEB UNM students, with a sample of 105 respondents determined using the proportionate stratified random sampling technique. Data were collected via questionnaires and analyzed using path analysis with SPSS software. The results show that: (1) Financial literacy and family financial education have a positive and significant effect on financial management behavior, both directly and indirectly. (2) Peers do not have a direct influence on financial management behavior but have a significant indirect effect through financial self-efficacy. (3) Financial self-efficacy is proven to be a crucial mediator, acting as a partial mediator for financial literacy and family education, and as a full mediator for the influence of peers. These findings emphasize that knowledge and social influence require self-confidence (efficacy) to transform into responsible financial management behavior in the digital era.